Wideband antenna gain enhancement based on metamaterial for 5G application - Khadidja Slimanefissa; Hala Guenfoud; Chaker SALEH (Université Amar Thelidji- Laghouat.FACULTE : TECHNOLOGIE.DEPARTEMENT : ELECTROTECHNIQUE, 2021)
Among the most important metamaterial application in the antenna field we can cite the antenna performances enhancement and size reduction .However, Antenna characteristics wideband’s a major objective of metamaterial used in the antenna field. We are interested in this work, with, a novel miniaturized metamaterial unit cell for 5G applications. The new structure is composed of an SRR with four slots, this metamaterial a bandwidth of 52.32% A set of unit cells are periodically associated on a substrate, above amicrostrip antenna with new dual slots in the operating frequency band 27GHz-31GHz. The results show that this metamaterial structure offers some interesting features performances, such as wide bandwidth, which makes the design suitable for 5G systems.
OPTION : Système de télécommunication